Tandem inverse-electron-demand hetero-/retro-Diels-Alder reactions for aromatic nitrogen heterocycle synthesis. - Foster, R; Willis, M (2013)
The merged inverse-electron-demand hetero-Diels-Alder (ihDA)/retro-Diels-Alder (rDA) reaction sequence can be used to rapidly synthesise highly functionalised nitrogen heteroaromatics. The reaction offers many advantages: high atom economy, high levels of regioselectivity, it rarely requires a catalyst and, in some cases, can be performed in the absence of solvent. In this tutorial review we discuss the range of commonly used dienophiles and aza-dienes for this process whilst highlighting the reactivity trends, and illustrating their applications.